ANALISIS PENGARUH KUALITAS AUDITOR TERHADAP EARNINGS RESPONSE COEFFICIENT (ERC)PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - darmajaya, lp4m ibi (Jurnal Manajemen dan Keuangan, 2011)
The purpose of this research to empirically examine the influence of auditor quality toward Earnings Respose Coefficient (ERC) at manufacture companies listed in Indonesia Stock Exchange. This research using quantitative analysis method through approach to calculation numbers of secondary data obtained from annual financial statements obtained from Indonesian Stock Exhange (IDX). The value of Earnings Response Coefficient (ERC) measured by Comulative Abnormal Return regression with Unexpected Earnings. Auditor quantity in this research measured by using 1 value dummy variable for companies with financial statements that audited by KAP Big 4 and 0 value for companies with financial statements that audited by KAP non Big 4 who subsequently converted into SPSS version 16. Testing is done by using sample linier regression test method. The sample of this research is 31 companies with observation number amount 155 financial statements. Monitoring was done during 5 years 2005, 2006, 2007, 2008, and 2009. The conclusion of this research shows that auditor quality does not influence toward Earnings Response Coefficient (ERC) at manufacture companies that listed in Indonesian Stock Exchange. Keyword: Earnings Response Coefficient (ERC), Auditor Qualtity